293 MICROARRAY ANALYSIS OF PROTEINS INVOLVED IN SIGNAL TRANSDUCTION AND APOPTOSIS IN SKELETAL MUSCLE OF PATIENTS WITH KETOSIS-PRONE TYPE 2 DIABETES MELLITUS. Issue 1 (1st January 2007) - Gosmanov, A. R.; Smiley, D.; Robalino, G.; Umpierrez, G. E.; Thomason, D. B.
Abstract : Most obese African Americans with diabetic ketoacidosis (DKA) exhibit clinical and metabolic features of type 2 diabetes and are able to discontinue insulin therapy during follow-up. These patients are characterized as having ketosis-prone type 2 diabetes mellitus (KPDM). To examine the underlying mechanisms, we examined changes in phoshorylation and expression of apoptotic and signaling proteins in skeletal muscle in patients with KPDM. Methods: Six obese normoglycemic subjects (control group) and seven patients presenting with blood glucose (BG) > 400 mg/dL and/or DKA underwent percutaneous needle biopsy of the vastus lateralis muscle. Muscle biopsies were homogenized in protein lysis buffer and samples from each group were analyzed in duplicate using a commercial antibody microarray. The microarray slides contained antibodies against 350 proteins involved in cell signaling and apoptosis. Changes in phosphorylation or expression by at least 40% were considered significant. Results: KPDM subjects (age 37 years, BMI 39.6 kg/m 2 ) had an admission blood glucose 564 mg/dL and HbA1c 11.4%, whereas age- and BMI-matched controls had a BG 84 mg/dL. In KPDM patients, hyperglycemia was associated with increased phosphorylation of six isoforms of PKC and with elevated muscle expression of four isoforms of protein phosphatases, signaling through Src, Shc1, MEK1/2, MEK3/6, RSK1/2, and activation of inhibitors of apoptosis STAT 1, 3, and 5. In patients with KPDM, we observed a decrease in phosphorylation and expression of antiapoptotic and proinflammatory proteins IKKalpha and NFkappaB p65, associated with reduced p53 expression. The abundance of heat shock proteins Hsp70, 47, 40, 20, 27 and GRP 57, 94 also decreased. In addition, there was reduced phosphorylation and expression of proapoptotic JAK2, JNK MAPK, jun, and STE20-like proteins. Conclusion: Compared with nondiabetic subjects, skeletal muscle from patients with KPDM at presentation were characterized by alterations in phosphorylation and expression of proteins involved in intracellular signaling, trafficking, regulation of apoptosis, and stress response. Preliminary analysis of the data indicates that hyperglycemia is associated with predominant activation of antiapoptotic mechanisms, which contrasts previously described effects of hyperglycemia in other cell types. Supported by grants from the ADA (7-03-CR-35) and NIH: R03 DK073190-01, K12-RR017643, and GCRC M01 RR-00039.